2022
DOI: 10.1001/jamanetworkopen.2022.4840
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Radiation Therapy Among Patients Enrolled in a Multidisciplinary Pulmonary Nodule and Lung Cancer Screening Clinic

Abstract: Key Points Question Is there a role for radiation oncologists in the evaluation and workup of pulmonary nodules, and what is the value of radiation therapy in a lung cancer screening population? Findings In this prospective cohort study of 1150 patients referred to a pulmonary nodule and lung cancer screening clinic, more than one-fourth of patients were recommended to undergo therapeutic intervention with surgery or radiation therapy, with most receiving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, other screening centers also have found that patient characteristics differ between the NLST and real-world programs 13 and an increasing proportion of all patients with stage I lung cancer are being treated with SBRT. 14 , 15 This suggests that our experience may be occurring on a much larger scale. With widespread implementation of LCS, evaluating outcomes for diverse patients who undergo different treatments will be critical for optimizing the balance of benefits and risks.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, other screening centers also have found that patient characteristics differ between the NLST and real-world programs 13 and an increasing proportion of all patients with stage I lung cancer are being treated with SBRT. 14 , 15 This suggests that our experience may be occurring on a much larger scale. With widespread implementation of LCS, evaluating outcomes for diverse patients who undergo different treatments will be critical for optimizing the balance of benefits and risks.…”
Section: Discussionmentioning
confidence: 89%
“…Under current guidelines, millions of patients in the US could miss out on a lifesaving screening LDCT simply because they may not be optimal surgical candidates. As shown by Milligan et al, 6 nonoperative interventions, such as SBRT, are critical tools to have available for the medically diverse early-stage lung cancer population, and an expanded menu of treatment options seems likely to lead to better tailored recommendations for individual patients. During multidisciplinary decision-making, we should ensure that radiation oncologists have a seat at the table.…”
mentioning
confidence: 99%